Geographical miss is associated with vulnerable plaque and increased major adverse cardiovascular events in patients with myocardial infarction. Issue 3 (3rd November 2015) - Calvert, Patrick A.; Brown, Adam J.; Hoole, Stephen P.; Obaid, Daniel R.; West, Nick E.J.; Bennett, Martin R.
Abstract : Objectives: To determine the incidence, characteristics, and outcomes associated with geographical miss (GM) of plaque. Background: GM describes plaques that are incompletely covered following stenting, with GM thought to be associated with worse clinical outcomes. However, the incidence and characteristics of intravascular ultrasound (IVUS)‐defined GM plaques have never been studied and the relationship between GM with both short and long‐term clinical events is unknown. Methods: One hundred and seventy patients with stable angina ( n = 100) or myocardial infarction (MI) ( n = 70) underwent virtual‐histology IVUS (VH‐IVUS) prior to, and following, percutaneous coronary intervention (PCI). GM was defined as three consecutive uncovered VH frames, either proximal or distal to the stented segment with plaque burden >40%. MACE was defined as a composite of death, myocardial infarction, unplanned revascularization, or hospitalization for angina. Results: In total, 245 plaques underwent PCI with 80 (32.7%) displaying evidence of GM (69 patients). GM was associated with increased plaque volume ( p < 0.001), % necrotic core, and dense calcium (both p < 0.001) and VH‐defined thin‐cap fibroatheroma (VH‐TCFA) ( p = 0.01). GM was not associated with increased periprocedural MI ( p = 0.15) or inflammatory cytokine release. At follow‐up, 42 MACE occurred in 28 patients (median 1, 115 days). MACE was attributable to 8/80 (10%) plaques with and 7/165 (4.2%) plaques without GM (log‐rank p = 0.11). GM was associated with increased MACE in patients presenting with MI ( p = 0.015), but not for those with stable angina ( p = 0.94). Conclusions: GM is common after PCI and associated with more vulnerable plaque composition/subtype. GM may confer a worse prognosis in patients undergoing PCI for MI. © 2015 Wiley Periodicals, Inc.